Novel BPI3Vc-vectored surface displayed fusion and hemagglutinin-neuraminidase antigens elicit broadly neutralizing antibodies in cattle - Sang, Huldah; Kim, Tae; Kumar, Rakshith; McCall, Jayden; Abraham, Aloysius; Koynarski, Tsvetoslav; Zajac, Michelle; Abdelsalam, Karim W.; Hernandez Muguiro, Daniela; Bauer, Katherine; Plattner, Brandon L.; Mwangi, Waithaka (Frontiers in Immunology, 2026)
Bovine parainfluenza-3 virus (BPI3V) contributes to Bovine Respiratory Disease Complex, causing severe pneumonia and death in cattle, leading to economic losses. Existing BPI3V commercial vaccines, based on genotype A strains, confer protection against some, but not all, genotype A strains and induce low neutralizing antibody titers against genotypes B and C. This study aimed to develop a live vaccine capable of inducing broad protection against diverse BPI3V strains using an attenuated BPI3V vaccine vector based on a genotype C strain. A rescued recombinant BPI3VcmutantGFP virus exhibited a temperature-sensitive attenuated phenotype in vitro. Novel Fusion (designated F2) and Hemagglutinin-Neuraminidase (designated HN2) antigens, derived from consensus protein sequences of BPI3V genotypes A, B, and C, were used to develop a recombinant prototype vaccine, designated rBPI3VcmutF2-HN2. The recombinant virus replicated efficiently, displayed the novel antigens on the surface of infected cells, and remained stable over nine in vitro passages. Intranasal vaccination of calves with the rBPI3VcmutF2-HN2 virus induced strong systemic and mucosal IgG responses against BPI3V genotypes A, B, and C, which were significantly amplified upon boost, unlike the responses elicited by a commercial vaccine. Notably, sera from calves vaccinated with the rBPI3VcmutF2-HN2 virus had significantly higher (p<0.0001) neutralizing antibodies against BPI3V genotypes A-C compared to the commercial vaccine. The F2-HN2 antigens were critical in eliciting neutralizing antibodies against wild-type BPI3Va and c (p< 0.0001), and BPI3Vb (p<0.001). Upon challenge with wild-type BPI3V genotype C virus, the rBPI3VcmutF2-HN2-vaccinated calves shed the least amount of virus in nasal swabs, had lower viremia, and exhibited minimal pulmonary lesions. Therefore, rBPI3VcmutF2-HN2 virus is a promising vaccine candidate that has potential to confer broad protection against multiple BPI3V strains.